Co-pyrolysis of biomass and waste tires under high-pressure two-stage fixed bed reactor. (January 2022) - Wang, Fengchao; Gao, Ningbo; Magdziarz, Aneta; Quan, Cui
Graphical abstract: Highlights: Pressurized pyrolysis of pine sawdust and side wall rubber was studied. SWR/PS pressurized co-pyrolysis with CBA aided in the capture of CO2 . The pine sawdust chars obtained under high-pressure shows melting problem. The LHV of syngas increased about 3.65 times after the catalytic process. Abstract: The distribution of biomass pyrolysis products under high pressure have rarely been reported. In this study, the effect of pressure on the product distribution of pine sawdust (PS) pyrolysis was studied. The synergistic effect of the side wall rubber (SWR) and PS was confirmed under pressurized conditions. Calcined bottom ash (CBA) and SWR char (SWRC) were used to enhance the quality of the pressurized co-pyrolysis products. The PS and SWR pyrolysis chars obtained under high pressure conditions exhibited serious melting and cross-linking problem. The CO2 content decreased to 19.96 vol% in co-pyrolysis gas with the CBA/SWRC7/3 catalyst. The water content decreased by 85.71% after the SWRC catalyst in the pressurized co-pyrolysis process. Compared with the concentration of benzene in PS and SWR oil, the concentration of benzene in SWR/PS7/3 oil without catalysts increased by 9.57 times and 0.25 times, respectively.